2022
DOI: 10.3389/fnut.2022.984695
|View full text |Cite
|
Sign up to set email alerts
|

Morchella esculenta mushroom polysaccharide attenuates diabetes and modulates intestinal permeability and gut microbiota in a type 2 diabetic mice model

Abstract: Type 2 diabetes mellitus (T2DM) is a health issue that causes serious worldwide economic problems. It has previously been reported that natural polysaccharides have been studied with regard to regulating the gut microbiota, which plays an important role in T2DM. Here, we investigate the effects of Morchella esculenta polysaccharide (MEP) on a high-fat diet (HFD) and streptozotocin (STZ)-induced T2DM in BALB/c mice. The administration of MEP effectively regulated hyperglycemia and hyperlipidemia and improved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Tiepishihu Xiyangshen granules showed prominent immunomodulatory activities by regulating TLR4/MAPK and PI3K/AKT/FOXO3a signal pathways [ 21 ]. However, gut microbiota and the intestinal barrier have important roles in chronic human diseases, which should not be ignored [ 22 ]. Therefore, the research focusing on effective methods to improve intestinal barrier function and repair the gut microbiota dysbiosis for immunodeficiency treatment is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Tiepishihu Xiyangshen granules showed prominent immunomodulatory activities by regulating TLR4/MAPK and PI3K/AKT/FOXO3a signal pathways [ 21 ]. However, gut microbiota and the intestinal barrier have important roles in chronic human diseases, which should not be ignored [ 22 ]. Therefore, the research focusing on effective methods to improve intestinal barrier function and repair the gut microbiota dysbiosis for immunodeficiency treatment is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Streptococcus , Facklamia , and Bosea were previously reported to be higher in people with an over-richness of bacteria in the intestine [ 61 ], type 2 diabetic animals [ 62 ], and mice with nonalcoholic fatty liver disease [ 63 ], respectively. The higher abundance of those three genera in the post-parturition Bangor Sewa sheep further indicated the changes in the physiological environment of the genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Streptococcus is positively correlated with obesity, inflammation and weight gain, and is found to be decreased in the HFS diet-induced obese mice through the effect of SCFA, 87,88 while Facklamia is an opportunistic genus that tends to increase in abundance in obesity-related problems such as type-2 diabetes and insulin resistance. 89 Furthermore, different authors have established a positive relationship between the abnormal increase in body weight, visceral fat, fat mass, and the abundance of Acinetobacter. 88,90 Additional authors have reported that a Sanghuangporus vaninii mixture ameliorated obesity related type-2 diabetes and altered intestinal microbiota by reducing the abundance of Odoribacter.…”
Section: Food and Function Papermentioning
confidence: 99%